Methane efflux from bubbles suspended in ice-covered lakes in Syowa Oasis, East Antarctica - Sasaki, Masafumi; Imura, Satoshi; Kudoh, Sakae; Yamanouchi, Takashi; Morimoto, Shinji; Hashida, Gen (Journal of Geophysical Research, 2009)
This is the first estimation of methane efflux from bubbles in lake ice in Antarctica. Bubbles suspended in shallow ice in 20 lakes were observed as part of the operations of the 45th Japanese Antarctic Research Expedition in ice-free rocky areas along the eastern coast of Lutzow-Holm Bay (Syowa Oasis) in East Antarctica in 2004. Anomalous methane concentrations in bubbles suspended in lake ice and anomalous dissolved methane concentrations in lake water were frequently found. Methane concentrations in bubbles varied of five orders of magnitude, from 1.9 ppmv to 18% v/v. A procedure that makes estimations of methane flux from ice-bubbles possible has been developed, based on a relationship between bubble-density distribution, brightness observed by digital photographs and methane concentration in bubbles. Such a procedure applied to Lake Oyako Ike in the Skarvsnes area, where the maximum methane concentration was observed, suggests that total bubble volume is about 0.6% of ice volume and the mass of methane in bubbles in the lake is about 74 kg. Almost all gases in bubbles are released to the atmosphere in the early ice melt season (a period of a few weeks in December and January). By applying area fraction frequency distributions to methane concentration ranges for 20 lakes surveyed, extrapolation to the whole Syowa Oasis, including 110 lakes, would give a provisional estimate of total emission of about 2 tons-CH4/yr. journal article